Mataloko Geothermal Power Plant Development Strategy in order to Maintain the Sustainability of Supply and Demand Electric Energy in Kupang, East Nusa Tenggara (A System Dynamics Framework) - Aditya, Addin (UIR PRESS, 2017)
One of Indonesia’s problem as an archipelagic country is unequally electrification ratio, especially in Indonesia eastern region. In 2015, the electrification ratio in Kupang is 58.67%. This figure is far below from Indonesia electrification ratio, which is 88.3%. At present, people of Kupang get their electricity supply from fuel energy power system, which is costly and has a bad impact for environment. Furthermore, Indonesia has many renewable resource that has not been fully utilized and this condition in line with acceleration program of electricity infrastructure development in Indonesia, considering that Kupang has a geothermal potential in Mataloko. This research aims to develop a dynamical model of Mataloko geothermal power plant 1 x 2.5 mw development strategy in Kupang, East Nusa Tenggara from technical and economical aspect. We used system dynamics to modelling the existing electricity condition in Kupang as a base model to develop scenarios. We hope this scenario can be taken as consideration to develop a renewable resource power plant in order to fulfill the electricity demand. The result shows that geothermal potential in Mataloko is feasible to generate an electricity